Transforming Traditional Businesses into Digital Marketplaces with the Latest Modern Management and Marketing Approaches - Djawa, Sutrisno; Rahman, Wahyudin Rahman (JBTI : Jurnal Bisnis : Teori dan Implementasi, 2025)
Traditional businesses in Indonesia face significant challenges in adapting to the digital economy due to their limited understanding of digital marketing, data utilization, and technology-based operations. This urgent research aims to bridge the gap between digital technology adoption and business performance, particularly in the digital marketplace. The objective is to analyse how modern digital marketing strategies and transformation management contribute to the successful transition of traditional businesses to competitive digital platforms. A quantitative, correlational approach was used, covering 270 MSMEs that have transitioned to the digital marketplace. Data were collected through structured questionnaires, direct observation, and documentation. Validity and reliability tests were conducted to ensure instrument quality, followed by statistical analysis using the Pearson correlation coefficient and multiple linear regression. The results indicate that digital transformation management and modern digital marketing strategies have a significant impact on the success of business transformation. MSMEs implementing depersonalized promotions, customer data analysis, automated systems, and search engine optimization (SEO) experienced increased customer loyalty, operational efficiency, and market reach. This transformation was supported by internal leadership, digital training, and adaptation to technological changes. In conclusion, an integrated approach combining strategic marketing and digital management is crucial for maintaining competitiveness in the digital marketplace. The importance of Marketing 5.0, change management theory, and innovation diffusion in explaining digital business adaptation. Implications: Some stakeholders are promoting structured digital strategies and policy interventions to accelerate the transformation of MSMEs in Indonesia.